2018
DOI: 10.1039/c8py00233a
|View full text |Cite
|
Sign up to set email alerts
|

Converting natural rubber waste into ring-opening metathesis polymers with oligo-1,4-cis-isoprene sidechains

Abstract: A chemical recycling of natural rubber waste via a degradation/ polymerisation approach is described. The vulcanized rubber waste was degraded by cross metathesis with ethyl acrylate as the key-step yielding enoate end-capped oligo-cis-isoprenes, which were subsequently converted into norbornenes via a cycloaddition reaction with cyclopentadiene. Ring-opening Metathesis Polymerisation (ROMP) then yielded main-chain unsaturated polymers bearing oligo-1,4-cis-isoprene side chains with appealing thermal stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…S2). [14] Characteristic peaks in the 1 H-NMR comprise a doublet of triplet at 6.94 ppm and a doublet at 5.82 (protons of the electron deficient double bond in E configuration) and a broadened signal from 5.30-5.00 ppm (olefinic protons of the oligoisoprene). The signal for methyl ester group gives rise to a singlet at 3.72 ppm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). [14] Characteristic peaks in the 1 H-NMR comprise a doublet of triplet at 6.94 ppm and a doublet at 5.82 (protons of the electron deficient double bond in E configuration) and a broadened signal from 5.30-5.00 ppm (olefinic protons of the oligoisoprene). The signal for methyl ester group gives rise to a singlet at 3.72 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…1). [14] Based on these results, we herein strive for exploring further applications of semi-telechelic oligomeric 1,4-cis-isoprenes containing α,β-unsaturated ester end-groups. Specifically, we aim at saponification of the ester group.…”
Section: Introductionmentioning
confidence: 98%
“…The compound mixture 1 was characterized using 1 H-and 13 C-NMR spectroscopies, and results match with literature (Figure S2, Supporting Information). [14] Characteristic peaks in the 1 H-NMR comprise a doublet of triplet at 6.94 ppm and a doublet at 5.82 (protons of the electron-deficient double bond in E configuration) and a broadened signal at 5.30-5.00 ppm (olefinic protons of the oligoisoprene). The signal for methyl ester group gives rise to a singlet at 3.72 ppm.…”
Section: Preparation Of the Amphiphilementioning
confidence: 99%
“…Ring‐opening metathesis polymerization (ROMP) of the resulting norbornene‐bearing oligomers finally yielded polymers with similar thermal characteristics as natural rubber ( Figure ). [ 14 ] Based on these results, we herein strive for exploring further applications of semi‐telechelic oligomeric 1,4‐ cis ‐isoprenes containing α , β ‐unsaturated ester end groups. Specifically, we aim at saponification of the ester group.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the unprotected free alcohols were effective CTAs for the cross metathesis degradation of NR; the obtained diol oligomers were useful materials of synthesizing polyurethanes, which can be used in flame retarding materials. Abbas et al 27 described an approach of preparing a norbornene derivative with oligo‐isoprene side chains via a strategy of cross metathesis followed by ring opening metathesis polymerization. NR was degraded via cross metathesis using ethyl acrylate as CTA to produce enoate end group oligo‐isoprene, which could react with cyclopentadiene via cycloaddition reaction.…”
Section: Introductionmentioning
confidence: 99%